Lexical Areas and Linguistic Domains in the Northwest of the Iberian Peninsula - Negro Romero, Marta; Sousa, Xulio (Madrygal. Revista de Estudios Gallegos, 2019)
Language atlases are an excellent source of data about the geographical distribution of language varieties and how they interact, once they have mapped recurring variants in different areas associated with the same variable. Despite the value of such works and the wealth of information they provide to researchers in a range of linguistic subdisciplines, few studies have made use of them to explore contact between linguistic domains. Two reasons for this are the difficulty of processing cartographic data and a lack of awareness of the valuable information that such materials contain. This paper presents the results of an exploratory analysis of a small set of items in the lexical section of the part of the Atlas Lingüístico de la Península Ibérica (ALPI) that covers the northeast of the Iberian Peninsula, where several distinct Romance languages coincide. The selected lexical variants have to do with ten concepts involving parts of the human body. The results of an analysis of the linguistic variants are compared and related to previous studies of the borders between the language areas covered, in order to chart similarities and correspondences in the distribution of variants at different levels of geolinguistic analysis and to identify the distribution patterns of variants.